Envelhecer em instituição de longa permanência privada: significados atribuídos pelas idosas, familiares e profissionais de saúde. - Salgueiro, Claudia Daniele Barros Leite (2021)
This thesis aimed to understand how the dwelling in a Long Term Care Institution for the Elderly (LTCI), from the perspective of the elderly, their relatives and institutional caregivers, in the light of Lifespan Theory, seeks to demonstrate that aging can be healthy and productive. Considering that healthy aging does not only concern the elderly, but also the context in which it is inserted, and the resources it receives to be able to age well and healthy, the analysis of this thesis also refers to the Perspective Aging in Place (AIP). This thesis is structured with three distinct but interrelated scientific studies. The first article deals with an integrative review of the literature on Aging in Long Term Care Institution (LTCI) from the Aging in Place Perspective (AIP). This study aimed to show the profile of the published works, both nationally and internationally, from 2002 to 2017, with a survey made from the Regional Portal of the Virtual Health Library (BVS), targeting journals indexed in the MEDLINE, LILACS and Index Psychology - Technical-scientific journals. Study 2 is a research of a qualitative and exploratory nature, in which an interview with a semi-structured script was carried out and a biossociodemographic questionnaire with seven elderly women who chose to live in LTCI. In the light of the Perspective of Aging in place (AIP), were analyzed the perceptions of the experiences of the elderly women who chose to reside in a LTCI. Study 3 analyzed the perceptions of accompanying family members (4) and health professionals (4) about the experiences of elderly women who chose to reside in a LTCI. Data from studies 2 and 3 were analyzed according to the Thematic Content Analysis Technique. The analysis also counted on the impressions noted in the research diary. Regarding the results, in study 1, the biopsychosocial issues discussed in the articles were: 1) Factors and reasons that influence the decision to reside in an institution; 2) The feelings and meanings of aging at home or at LTCI; 3) Aging at home or at LTCI: family, social involvement and identification with the home. In study 2, it was evidenced that in the narratives of the elderly the discourses were summoned and grouped into four thematic categories: 1) Aging and living in a LTCI; 2) Aging in LTCI - Identity with the site; 3) Aging in LTCI and networks of relationships; 4) Aging in LTCI: Feelings and emotions. Regarding the contents of the accompanying family members and health professionals interviewed in study 3, situations were mentioned which were grouped into four broad themes, namely: I) Identification, belonging to the place and satisfaction with the dwelling; 2) Maintenance of independence and autonomy, health conditions; 3) Social participation and felt needs; 4) Positive vision, plans and learning. The data obtained in this research indicate that, in addition to being proactive and with a good family and social role, the elderly women showed identification with the place and feeling of belonging. It can be concluded that aging in an LTCI can be rewarding, depending on the quality of the institution, the established links and the adaptability to the stage of life in which they are found.